The Influence of Human Resources in Improving The Quality of Education Through Training And Career Development of Teachers in Palopo City - Nurul Azisah; Ilham Tahier; Muh Yusuf (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The article titled "The Influence of HRM in Improving Education Quality through Training and Career Development of Educators in Palopo City" aims to analyze the impact of human resource management (HRM) on education quality, particularly through training and career development of educators. This study involved 97 respondents, with data collected using questionnaires. The data were analyzed using multiple linear regression with the assistance of SPSS Statistics 22 software. The findings of the study reveal that: 1. Human resource management has a positive and significant influence on education quality. 2.Training has a positive but not significant influence on education quality. 3. Career development has a positive and significant influence on education quality. 4) simultaneously variable X influences variable Y